Pengalaman belajar - Mengajar Guru-Guru Pelatih Universiti Sains Malaysia - Mohamed, Abdul Rashid (Penerbit Universiti Sains Malaysia, 2000)
This study tried to take a peek at the experience of a group of USM student teachers undergoing their teaching practice. The researchers were interested to find out what went on in the absence of the USM supervisors.